Introduction to psychology practice tests - Landrum, R. Eric (McGraw-Hill College, 1999)
These multiple-choice practice tests give you a glimpse of the type of test questions you may encounter on the material covered in an Introduction to Psychology course. The practice tests provide a sample of the types of questions that often appear on exams. Each chapter begins with a list of learning objectives to guide your studying. The questions will be similar to those found on exams, but it is doubtful an instructor would use these exact questions. For futher study aids, see if your particular textbook offers a student study guide.